2012
DOI: 10.3171/2012.6.focus12110
|View full text |Cite
|
Sign up to set email alerts
|

Petrosal approaches to brainstem cavernous malformations

Abstract: Object Although they provide excellent ventral and lateral exposure of the brainstem, petrosal approaches to brainstem cavernous malformations (CMs) are infrequently reported. Methods The authors reviewed their experience with petrosal approaches to brainstem CMs in combination with a comprehensive review of the literature to elucidate resection rates, complication rates, and outcomes. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…Other predictors included surgery within 1 year of seizure onset, CM size less than 1.5 cm, solitary CMs, partial seizures only and medical control of the seizures preoperatively. Overall 1.6-3.1% [10,12,14] Incidental CM 0.08-0.2% [5,32] Any unruptured CM 0.3-0.6% [10,12,33,34] Ruptured CM 4.5-22.9% [5,10,12,[33][34][35] Ruptured, within first year 14-18% Resection of eloquent CMs is a subject of significant neurosurgical interest as supratentorial deep CMs and brainstem CMs require both creative and meticulous surgical approaches and technique to allow for successful resection with minimal operative morbidity [18][19][20][21][22][23][24]52,53,[55][56][57][58]. Most of these lesions would be considered 'grade III' CMs in the scheme of Kivelev and colleagues.…”
Section: Surgical Excisionmentioning
confidence: 99%
“…Other predictors included surgery within 1 year of seizure onset, CM size less than 1.5 cm, solitary CMs, partial seizures only and medical control of the seizures preoperatively. Overall 1.6-3.1% [10,12,14] Incidental CM 0.08-0.2% [5,32] Any unruptured CM 0.3-0.6% [10,12,33,34] Ruptured CM 4.5-22.9% [5,10,12,[33][34][35] Ruptured, within first year 14-18% Resection of eloquent CMs is a subject of significant neurosurgical interest as supratentorial deep CMs and brainstem CMs require both creative and meticulous surgical approaches and technique to allow for successful resection with minimal operative morbidity [18][19][20][21][22][23][24]52,53,[55][56][57][58]. Most of these lesions would be considered 'grade III' CMs in the scheme of Kivelev and colleagues.…”
Section: Surgical Excisionmentioning
confidence: 99%
“…4,5,10,[29][30][31]46,53,59,61 A lateral trajectory was preferred for lesions in the pons. 4,19,33,35,46,67 Electrophysiological monitoring of the cranial nerves (according to lesion location), somatosensory evoked potentials, motor evoked potentials, and brainstem auditory evoked potentials was performed routinely. Intraoperative neuronavigation was used in a few cases.…”
Section: Surgical Strategymentioning
confidence: 99%
“…Adding to the difficulty is the need to preserve the patient's hearing in order to maintain quality of life; a previous comprehensive review reported that 12% of patients who received an anterior petrosectomy due to brainstem cavernous malformations experienced perioperative hear- ing loss. 6 The incidence of hearing loss may be increased in proportion to the location of the lesion, size of the lesion, and the level of difficulty of the surgery.…”
Section: Resultsmentioning
confidence: 99%
“…The extent of petrosectomy has been widened from the time of introduction of this approach in the neurosurgical field until recently, and this approach is known to be effective for accessing ventral mid-to upper pontine lesions in particular. 1,[4][5][6]9 In fact, when performing the anterior petrosal approach in the narrow space of the parallelogram-shaped anterior surface of the petrous bone, which is bounded by V3, the GSPN, the superior semicircular canal, and the petrous ridge, only approximately 3 cm 2 may not present a straightforward procedure with a manageable learning curve. Adding to the difficulty is the need to preserve the patient's hearing in order to maintain quality of life; a previous comprehensive review reported that 12% of patients who received an anterior petrosectomy due to brainstem cavernous malformations experienced perioperative hear- ing loss.…”
Section: Resultsmentioning
confidence: 99%